The Impact of Home Gardening amidst Climate Change - Mobo, Froilan (International Journal of Multidisciplinary: Applied Business and Education Research, 2020)
Today’s climate is unpredictable there are so many natural calamities which took place in our country which is the Philippines, two weeks ago because of the sudden changes of the weather in the Province of Zambales, the Philippines a strong tornado hits the town of Cas-tillejos, Zambales which some of the electrical wirings were severely damaged because of the sudden change of the climate. The researcher is thinking of implementing a home gardening to each Municipality in our Province. By doing this it can help lessen the pollution in the air and it will help heal our Ozone Layer faster. The empirical evidence for the benefits of gardening and the advocate of the development and testing of socio-ecological models of community resilience through the impact of community gardens, especially in urban areas is highly effective (Okvat & Zautra, 2011). As lessening the air pollution will have a greater impact on our Ozone Layer no to deplete but it will heal the would faster. The present study revealed that local experiences in the face of climate change adaptation have merits that need special consideration (Anik & Khan, 2012). Also, the Researcher will imple-ment this project in the Municipality of Subic, Zambales.